Self-assembled nanofibers of perylene diimide for the detection of hypochlorite in water, bio-fluids and solid-state: exogenous and endogenous bioimaging of hypochlorite in cells. Issue 1 (28th November 2019) - Kumar, Kapil; Kaur, Sandeep; Kaur, Satwinderjeet; Bhargava, Gaurav; Kumar, Subodh; Singh, Prabhpreet
Abstract : PDI–DAMN shows the disintegration of nanofibers into flake-like aggregates with ' turn-on ' fluorescence response on the addition of ClO − in solid-state, bio-fluids and MG-63 cells. Abstract : A fluorescent probe PDI–DAMN based on perylenediimide containing diaminomaleonitrile at the bay -position was designed and synthesized for the detection of ClO − . PDI–DAMN self-assembled as nanofibers with diameters in the range of 100–200 nm in H2 O : CH3 CN (1 : 1). The addition of ClO − into PDI–DAMN resulted in the disintegration of nanofibers into flake-like aggregates of smaller size (50–80 nm) as supported by SEM and DLS data. The addition of ClO − to HEPES buffer–CH3 CN solution (1 : 1, v/v, pH 7.4) of PDI–DAMN caused a hypochromic effect on the ICT band at 528 nm and ' turn-on ' fluorescence enhancement at 508/554 nm due to the oxidative cleavage of –CN– bond. A linear correlation plot between the concentration of ClO − versus fluorescence intensity ( R 2 = 0.9968)/absorbance ( R 2 = 0.9988) in the concentration range 0–7 nM (fluorescence)/0–90 nM (absorbance) could determine ClO − with the detection limits of 1 and 10 nM, respectively. Optical studies performed on spiked urine and blood serum samples showed good estimation and recovery of ClO − (100 ± 5%). TLC-based test-strips coated with PDI–DAMN changed colour upon the addition of ClO − with detection as low as 7.44 ng cm −2 . The application of PDI–DAMN for the bio-imaging of both exogenous and endogenous ClO − in MG-63 cells with good biocompatibility has also been demonstrated. The detailed mechanism of the interactions of ClO − with PDI–DAMN using 1 H NMR titration, DFT studies and response mechanism of pH are also discussed.